"In the midst of economic disaster, can the USA still care about green accounting? .... Which is more important a sustainable economy or a sustainable environment?". (21st December 2010) - Crawford, Constance
The Obama administration has called for a heightened amount of transparency in financial reporting culminating from the recent debacle on Wall Street. Interestingly, as our economy wavers between recession and or depression, the worldwide economy is focused on gross domestic product or GDP which measures the total production and consumption of goods in our domestic economy (Curwood, 2004). How much transparency can there be reported when GDP does not include the costs of the 'greening of the economy?' Many of the costs and benefits associated with environmentally sound business practices are intrinsic in value and therefore difficult to place a realistic value on (Patrut et al., 2008) US generally accepted accounting practices or GAAP has resisted including contingent environmental assets to be reported on the balance sheet or environmental cost savings on the income statement because they have no GDP value (Fuld, 2009).